Method of controlling a group of unmanned aircraft for searching and destruction of objects using artificial intelligence elements - Тимочко, О.; Тристан, А.; Матющенко, О.; Шпак, Н.; Двуліт, З.; Tymochko, O.; Trystan, A.; Matiushchenko, O.; Shpak, N.; Dvulit, Z. (Видавництво Львівської політехніки, 2022)
У статті розроблено метод управління групою безпілотних літальних апаратів для пошуку та знищення об’єктів противника. Метод полягає у розпізнаванні ситуацій та коригуванні дій групи відповідно до неї. Основою методу є використання інтелектуальної системи підтримки прийняття рішень. Метод управління групою безпілотних літальних апаратів для пошуку та знищення об’єктів побудований відповідно до концепції мультиагентних систем. Розроблено інформаційну технологію процесів методу управління групою безпілотних літальних апаратів за методологією IDEF0.

The article develops a method of controlling a group of unmanned aerial vehicles to search for and destroy enemy objects. The method is to recognize situations and adjust the actions of the group according to it. The basis of the method is the use of an intelligent decision support system. It provides situation recognition, using image recognition materials (intelligence materials), generalization of the obtained information and its comparison with the elements of the set of descriptions of typical situations. The method of controlling a group of unmanned aerial vehicles to search for and destroy enemy objects is built according to the concept of multi-agent systems – intelligent agents – UAVs. The information technology of processes of the method of control of a group of unmanned aerial vehicles according to the IDEF0 methodology is developed.
Метод управління групою безпілотних літальних апаратів з метою пошуку і знищення об’єктів з використанням елементів штучного інтелекту
Keywords: система управління; мультиагентна модель; штучний інтелект; група безпілотних літальних апаратів; пошук та знищення об’єктів; автономна система; локальні правила самоорганізації; розпізнавання ситуації; control system; multi-agent model; artificial intelligence; group of unmanned aerial vehicles; search for and destruction of objects; autonomous system; local rules of self-organization; situation recognition